Physical Elements in the film “A few Days in the Life of I.I. Oblomov” by N.S. Mikhalkov - Vojvodić, Jasmina, profesorica ruske književnosti (Array, 2013)
The present paper analyses physical elements in the film adaptation “A Few Days in the Life of I. I. Oblomov“, directed by N. Mikhalkov in 1979. Since the novel Oblomov by Goncharov is one code of “mono-code” medium, while the film is another, “multi-code” medium, we argue that film adaptation is a completely new artistic discourse. Finally, we analyse a series of relationships, such as those between Oblomov and Stoltz (friendship), Oblomov and Zakhar (one body), Oblomov and Olga (sexual relationship). All the mentioned relationships are represented through intensive visual body codes (tactile sensations), such as gestures, handshakes and kisses.